2018
DOI: 10.1126/sciadv.1701393
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the substrate proteins of U-box E3s E4B and CHIP by orthogonal ubiquitin transfer

Abstract: Engineering the ubiquitin transfer cascades by phage display enables an efficient way to profile E3 substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 73 publications
3
67
0
Order By: Relevance
“…We expressed human xUB, xUba1, and xUbcH5b or xUbcH7 in HEK293 cells and tested their orthogonality with wt E1 and E2 enzymes. We confirmed that xUB was exclusively loaded on xE1 or xE2 enzymes and it would not cross over to the wt cascade during the transfer (Wang et al, 2017a;Bhuripanyo et al, 2018). These studies established that we could use mutant transplantation to extend the OUT cascade across species and reach different E2 enzymes.…”
Section: The Concept Of Orthogonal Ubiquitin Transfersupporting
confidence: 60%
See 2 more Smart Citations
“…We expressed human xUB, xUba1, and xUbcH5b or xUbcH7 in HEK293 cells and tested their orthogonality with wt E1 and E2 enzymes. We confirmed that xUB was exclusively loaded on xE1 or xE2 enzymes and it would not cross over to the wt cascade during the transfer (Wang et al, 2017a;Bhuripanyo et al, 2018). These studies established that we could use mutant transplantation to extend the OUT cascade across species and reach different E2 enzymes.…”
Section: The Concept Of Orthogonal Ubiquitin Transfersupporting
confidence: 60%
“…xUbcH5b will not pair with either wt E4B or CHIP to mediate xUB transfer due to the mutations in the N-terminal helix of xUbcH5b that interferes with its binding to the U-box domain of the E3s (Benirschke et al, 2010). To identify U-box mutants complementary with xUbcH5b, we randomized residues in loop1 of E4B U-box that interact with K4E and K8E mutations in xUbcH5b (Bhuripanyo et al, 2018). We used phage selection to identify catalytic active mutants of E4B U-box based on xUB transfer (Fig.…”
Section: The Concept Of Orthogonal Ubiquitin Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…We previously engineered xUB-xUba1 and xUba1-xUbcH5b pairs to enable the exclusive transfer of xUB to xUbcH5b (Zhao et al, 2012). We recently used phage display to engineer an xUbcH5b-xCHIP pair that would deliver xUB to CHIP and then to its substrate proteins (Bhuripanyo et al, 2018). We expressed the OUT cascade of CHIP in the HEK293 cells with xUB tagged with 69 Histidine and biotin tags (HBT-xUB).…”
Section: Mot-2 Is a Substrate For The Chip E3 Ubiquitin Ligasementioning
confidence: 99%
“…UBE4B has been identified as an E3/E4 ligase that collaborates with Hdm2 to catalyze the polyubiquitination and degradation of the tumor suppressor p53 [32]. UBE4B has also been shown to ubiquitinate additional substrates such as EGFR, Ataxin-3 and OTUB1 [33][34][35]. To date, UBE4B has not been implicated in the ubiquitination of any viral proteins.…”
Section: K63-linked Polyubiquitination and Stabilization And Inhibitimentioning
confidence: 99%